When morphological ability exceeds syntactic ability: A case study. (1st February 2019) - Ingram, David
ABSTRACT: This article addresses the question of whether children classified as having a specific language impairment are such due to a particular problem in inflectional morphology. This has been claimed to be the case for some time. An effort is made here to propose that there may be an age effect behind that result. To support this possibility, a case study of a much older child with specific language impairment is presented. The participant is Tom, a child with a language impairment who underwent language intervention between the ages 9;4 and 10;3. During that period, language samples were taken at five different times (MLUs 5.3–6.0). They were analyzed to examine both Tom's morphological and syntactic abilities. The results indicated that he did quite well with English noun and verb inflections, but was unable to generate complex sentence structures. If there were a period when he had such difficulties, it was overcome by the time of the sampling. A lexical explanation is given which argues that bound morphology will appear better than syntax in cases where children are older and thus have had time to acquire the various inflected words as individual lexical items.